STARTING ADJECTIVES FOR METAL-POLYMERIC TRIBOSYSTEMS WITH COMPOSITION COVERAGE - V.A. KOHANOVSKY; U.V. SIDELNIK-RUBANOVA (Advanced Engineering Research, 2008)
Results of unseat moment investigations for metal-polymeric turning pairs are cited. Testing machine and testing technique are described. Fluent features of thermal and power load conditions to friction coefficient are descripted.